Analisis Biomekanika Gerakan AP-CHAGI Taekwondo Berbasis Teknologi Digital (Studi pada Atlet Pelatda Sumut) (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to introduce and analyze the effectiveness of the Yog-Ger digital application as an aid in evaluating the performance of taekwondo athletes, specifically in the front kick (ap-chagi) technique. Although sports biomechanics plays a crucial role in optimizing movement for peak performance, the limited use of digital technology often poses a major obstacle. Using a descriptive qualitative approach, this research involved one male athlete from the North Sumatra Taekwondo Provincial Training Camp as the sample. Kick motion data was analyzed using the Yog-Ger application to measure the angles and duration of each kick phase. The results indicate a disparity in timing between the initial phase (knee-up) and the final phase (landing). This disparity suggests a biomechanical inefficiency that can hinder performance and the transition to subsequent movements. The Yog-Ger application proved effective in providing prescriptive quantitative data, enabling coaches to design more specific training programs aimed at improving movement efficiency, speed, and kick power. In conclusion, this study demonstrates that leveraging digital technology like Yog-Ger is highly beneficial for the evaluation and technical development of taekwondo athletes.